2019
DOI: 10.1177/0391398819895287
|View full text |Cite
|
Sign up to set email alerts
|

Hemoadsorption treatment with CytoSorb® in patients with extracorporeal life support therapy: A case series

Abstract: Introduction: Extracorporeal life support is an increasingly used technique for respiratory and cardiocirculatory support. Besides primary organ dysfunction, an excessive systemic hyperinflammatory response can be the underlying cause for acute organ failure necessitating extracorporeal life support therapy, or it may be associated with the extracorporeal life support itself. Controlling this overwhelming inflammatory response using CytoSorb® hemoadsorption has been shown to be associated with improved hemodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Among survivors, vasopressor use decreased to 31.6% after 72 hours and to 26.3% after 96 hours compared to baseline. In accordance with previous studies [28,29,32,40,44] a rapid shock reversal was achieved (Fig. 5).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among survivors, vasopressor use decreased to 31.6% after 72 hours and to 26.3% after 96 hours compared to baseline. In accordance with previous studies [28,29,32,40,44] a rapid shock reversal was achieved (Fig. 5).…”
Section: Discussionsupporting
confidence: 92%
“…CytoSorb® e ciently removes a broad spectrum of toxic PAMPs and DAMPs from the blood [26,27] invitro, which could alleviate the negative consequences, such as capillary leakage to improve microcirculation and organ function in-vivo [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…after 96 hours compared to baseline. In accordance with previous studies [28,29,32,40,44] a rapid shock reversal was achieved (Fig. 5).…”
Section: Discussionsupporting
confidence: 92%
“…However, there are only limited prospective data with control groups available that investigate the elimination of cytokines using CS [21][22][23]. Although a decrease in cytokines was described by different authors [15,24], this could be due to causal therapy approaches such as anti-infective or supportive therapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Different authors showed a decrease in cytokines in patients treated with CS [14,15]; however, it remains unclear whether a comparable decrease would also have been observed without the use of CS, since control groups were missing. A randomized controlled trial recently published by Supady et al showed no difference in IL-6 reduction with and without CS in patients infected with Sars-CoV-2 and supported by extracorporeal membrane oxygenation [16].…”
Section: Introductionmentioning
confidence: 99%